2021
DOI: 10.15294/jejak.v14i2.32032
|View full text |Cite
|
Sign up to set email alerts
|

Public Behaviour on Cash Waqf: Evidence from Indonesia

Abstract: Despite the potential governmental agenda towards cash waqf, this area has been givessn limited attention in academic literature with special regards to the supply side. Therefore, this study aims to investigate the factors influencing the public intention in endowing cash waqf by utilizing an extended theory of planned behaviors (TPB); in which religiosity, knowledge, and trust variables are added. Primary data from 685 respondents in Indonesia are analyzed using structural equation modeling (SEM). The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 22 publications
(31 reference statements)
2
19
0
Order By: Relevance
“…Cash waqf has become a topical area among researchers on a global scale. Some previous studies related to cash waqf intention will be explored and supported in this study (Azizi et al, 2019;Dennis et al, 2018;Kasri & Chaerunnisa, 2020;Niswah et al, 2020;Niswah et al, 2019;Osman & Muhammed, 2017;Purnomowati et al, 2020;Syafira et al, 2020;Zabri & Mohammed, 2018;Haidlir et al 2021). However, there are only limited studies related to CWLS (Baiti & Syufaat, 2021;Hiyanti et al, 2020;Paul et al, 2021;Tanjung & Windiarto, 2021;Yasin, 2021).…”
Section: Previous Studies On Cash Waqf Intentionmentioning
confidence: 68%
See 1 more Smart Citation
“…Cash waqf has become a topical area among researchers on a global scale. Some previous studies related to cash waqf intention will be explored and supported in this study (Azizi et al, 2019;Dennis et al, 2018;Kasri & Chaerunnisa, 2020;Niswah et al, 2020;Niswah et al, 2019;Osman & Muhammed, 2017;Purnomowati et al, 2020;Syafira et al, 2020;Zabri & Mohammed, 2018;Haidlir et al 2021). However, there are only limited studies related to CWLS (Baiti & Syufaat, 2021;Hiyanti et al, 2020;Paul et al, 2021;Tanjung & Windiarto, 2021;Yasin, 2021).…”
Section: Previous Studies On Cash Waqf Intentionmentioning
confidence: 68%
“…The successful combination of waqf and Sukuk also needs to pay more attention to public trust in waqf institutions. Haidlir et al (2021) conducted a study that shows the urgency of such trust. They reported that integrity is first mediated by the reputation variable and explained that a more positive attitude, better supporting environment to participate in cash waqf, and a higher level of trust in waqf institutions significantly influenced the intention of people to endow cash waqf.…”
Section: Previous Studies On Cash Waqf Intentionmentioning
confidence: 99%
“…Recent studies (Haidlir et al, 2021;Iman et al, 2021;Ismaila & Maryantib, 2022;Osman et al, 2016;Ratnasari et al, 2017) have examined the donor's intention to contribute to waqf. Some of the empirical research (Haidlir et al, 2021;Ismaila & Maryantib, 2022;Osman & Muhammed, 2017;Osman et al, 2016) have adopted TPB and employed SEM and/or PLS in examining the donor's intention to contribute to waqf. Harahap et al (2020) established that SN, PBC, and religious commitment were influential on waqf behavior in the era of COVID-19.…”
Section: Tpb and Intention To Donate To Waqfmentioning
confidence: 99%
“…They documented the relevance of TPB in determining the intention to give cash waqf. Haidlir et al (2021) examined public behavior on cash waqf in Indonesia. Using extended TPB and SEM, it was revealed that TPB antecedents encouraged individuals' behavior towards waqf.…”
Section: Tpb and Intention To Donate To Waqfmentioning
confidence: 99%
“…But, in the end, it would cause poverty and inequality problems. Meanwhile, in Islamic social finance, there is the concept of zakah, which is one of the five principles of Islam which instructs Muslims to spend their wealth on the poor and needy (Ascarya et al, 2017;Haidlir et al, 2021). Not much different from zakat, waqf is one of the social finance instruments expected to bring prosperity and socio-economic balance to the community.…”
Section: Introductionmentioning
confidence: 99%